Exploring The Influence of Unforgettable Tourism Experience on Revisit Intention: The Mediating Role of Tourist Satisfaction - Agata, Muhamad Ikhsan; Ajeng Pramesti, Diesyana (UMSurabaya Publishing, 2025)
This research aims to analyze the mediating role of tourist satisfaction in the relationship between memorable tourist experiences and tourist experiences on their intention to return to the natural scenic destination of Ketep Pass. The research methodology adopts a quantitative approach, using questionnaires for data collection and Structural Equation Modeling (SEM) as an analysis technique. The research involved 110 respondents who had visited Ketep Pass at least twice. The study findings show an intention to revisit, and the analysis results show that tourist experience and satisfaction variables significantly influence this variable. Meanwhile, the effect of memorable experiences is not statistically significant. This research proves that efforts to create unforgettable experiences alone cannot guarantee that tourists will return. Managers need to pay attention to other more dominant factors, such as overall satisfaction and the unique characteristics of their destination